Unique Surgical Challenges in Early Life Epilepsy - Perry, Michael Scott; Hansen, Daniel (Seminars in Neurology, 2025)
The incidence of epilepsy is highest at the extremes of age. Drug resistance is present in approximately one-third of people with epilepsy but occurs at higher than average rates in children with seizure onset before age 3 years, owing to a variety of etiologies unique to this age group. Epilepsy surgery is an effective therapeutic option for drug-resistant epilepsy but is vastly underutilized. Epilepsy surgery in children under age 3 comes with distinct clinical challenges related to brain anatomy, evolving developmental maturation, and limitations of evaluation and surgical strategies. However, epilepsy surgery can lead to seizure freedom or significant seizure reduction in this age group. Early seizure control may have a significant positive impact on long-term cognitive development, making urgency of surgical referral of immense importance. This review highlights available evidence on the safety and efficacy of epilepsy surgery in early-life epilepsy, identifying barriers to surgical therapy, describing utilization of available evaluation and surgical strategies, and examining risks and benefits of earlier surgical consideration in this vulnerable population.
Keywords: drug-resistant epilepsy; epilepsy surgery; surgical morbidity